The intergenerational transmission of human capital: Exploring the role of skills and health using data on adoptees and twins - Petter Lundborg; Martin Nordin; Dan Olof Rooth (Institute for the Study of Labor (IZA), 2011)
In this paper, we focus on possible causal mechanisms behind the intergenerational transmission of human capital. For this purpose, we use both an adoption and a twin design and study the effect of parents' education on their children's cognitive skills, non-cognitive skills, and health. Our results show that greater parental education increases children's cognitive and non-cognitive skills, as well as their health. These results suggest that the effect of parents' education on children's education may work partly through the positive effect that parental education has on children's skills and health.
urn:nbn:de:101:1-201111213272
Keywords: I12; I11; J14; J12; C41; 330; intergenerational transmission; human capital; education; health; cognitive skills; non-cognitive skills; adoptees; twins; Humankapital; Generationenbeziehungen; Kinder; Eltern; Kognition; Gesundheit; Schätzung; Schweden